A Comparative Study: in Some Physical Traits between the Different Lines of Play in Quintet Football - Basma Abdul Hussein Shandal (Indian Journal of Forensic Medicine & Toxicology, 2021)
After the development in the level of mathematical achievement in its first version, it is the feature in the lives of peoples because numbers of players and raising their technical, physical, plans and psychological levels are the main goals for which training programs are built, especially attention to qualities more than others, such as strength distinguished by speed and speed of movement here, the importance of research varies. The most important importance of research. As for the most important characteristic of speed and kinetic speed, playing lines. As for the most important researcher, focusing on the page distinguished by speed and kinetic velocity and for all lines of play.